Building Peace in Swat Valley: A Qualitative Study of Multi-Stakeholder Involvement in Sustaining Peace - Yasin, Ayesha; Khan, Faiqa (Annals of Human and Social Sciences, 2024)
Peacebuilding is a multi-sphere and multi-tiered approach that helps to transform disputes in development opportunities for stakeholders. The research aims to investigate the stakeholders and their involvement in post-conflict peacebuilding in the swat area of Pakistan. The study explores the stakeholder’s mindset that comprises the local community, civil society, and government, with regard to peacebuilding process sustainability in the Swat. The main rationale is how to prevent militancy from reoccurring while also identifying and analyzing institutionalized and structural attempts to encourage peacebuilding in Swat by involving stakeholders. The qualitative research method, including Discourse studies and the constructivist philosophical paradigm, is utilized to know the stakeholder’s mindset towards the peace-building process and efforts after the destructive conflict in the area of Swat. A semi-structure proforma was prepared to conduct interviews. Six tehsils of Swat Valley were selected to get detailed and in-depth data. In selected tehsils thirty interviews were carried out based upon the conflict impacts on them. The study discovers that the social, economic, cultural, and political tiers regarding peacebuilding measures hardly attained their purpose in Swat. The gaps in the peace-building measures and lack of coordination within the institutions are significant hurdles that are required to be reduced regarding maintainable development activities in the Swat.